A new neurological entity manifesting as involuntary movements and dysarthria with possible abnormal copper metabolism. Issue 6 (1st December 2001) - Tagawa, A; Ono, S; Shibata, M; Imai, T; Suzuki, M; Shimizu, N
Abstract : A few patients with an affected CNS involving abnormalities in copper metabolism have been described that do not fit any known nosological entities such as Wilson's disease or Menkes' disease. Three sporadic patients (two men and one woman) were examined with involuntary movements and dysarthria associated with abnormal concentrations of serum copper, serum ceruloplasmin, and urinary copper excretion. The onset of neurological symptoms occurred at the age of 15 to 17 years. The common clinical symptoms were involuntary movements and dysarthria. The involuntary movements included dystonia in the neck, myoclonus in the shoulder, athetosis in the neck, and rapid orobuccal movements. The dysarthria consisted of unclear, slow, and stuttering speech. Two of the three patients did not have dementia. A cousin of the female patient had been diagnosed as having Wilson's disease and had died of liver cirrhosis. Laboratory findings showed a mild reduction in serum copper and ceruloplasmin concentrations, whereas urinary copper excretion was significantly reduced in all three patients. Two of the three patients showed a high signal intensity in the basal ganglia on T2 weighted brain MRI. In conclusion, the unique findings of involuntary movements, dysarthria, and abnormal serum copper and urinary copper concentrations suggest that the three patients may constitute a new clinical entity that is distinct from either Wilson's or Menkes disease.